Agglomeration spillover effects in German land and house prices at the city and county levels - Stefanie Braun; Gabriel S. Lee (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
We estimate spatial German land price effects using the county-level residential land prices from 2014 to 2018. We show that county-level spatial agglomeration effects play a large and significant role in explaining the cross-county variations in land prices. For example, a 1 % increase in the median income has an increase of 3.45 % in land prices, whereas a 1 % increase in the population density accounts for an increase of 5.47 % increase in land prices. We find that similar empirical patterns also hold for house prices but less so for the seven major German cities. Moreover, housing supply factors such as the available land to build and housing stocks are crucial factors in explaining land and house prices. Furthermore, we show that the land price spillover effects are among the dominating factors in the formation of regional house prices. These results suggest that changes in agglomeration variables such as median income (productivity) and population density cannot completely explain disparate local land and house prices. Lastly, estimating two different land price measurements for Germany shows that direct and indirect agglomeration spillover effects can explain more variation in residential land prices than vacant land prices.
Keywords: R0; R11; R14; R21; R31; 330; German Land prices; Land values; German Housing prices; Housing values; Spatial Effects